The Influence of Customer Orientation on New Product Development with Moderating Environmental Factors on MSME in Tulungrejo Village, Batu City - Ivana Angela; Anna Triwijayati; Erica Adriana (Jurnal Ekonomi dan Bisnis Digital, 2023)
MSMEs (Micro, Small and Medium Enterprises) are an important sector in the Indonesian economy. Because Tulungrejo Village is a village that has a lot of tourism, it is very important for MSMEs in Tulungrejo Village to further prioritize the development of new products and customer needs. The purpose of this study is to help MSMEs in knowing the needs and desires of customers. In addition, it is also hoped that MSMEs can continue to innovate to develop ideas both in making new products and old products that are renewed.  This research uses quantitative methods and the data source in this study uses a questionnaire filled out by 66 respondents from MSMEs in Tulungrejo Village. The study found that there is a positive influence of customer orientation on new product development at MSMEs with moderating environmental factors in Tulungrejo Village.